PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR TEMA 5 SUBTEMA 2 PEMBELAJARAN 1 SISWA KELAS V SDN OELASIN - Dimas Elison Manuain; Angelikus Nama Koten; Maxsel Koro (Universitas Nusa Cendana, 2023)
This study aims to improve student learning outcomes by applying the Contextual Teaching and Learning model in learning on theme 5 sub-themes 2 learning 1 in class V of SD Negeri Oelasin, Rote Ndao Regency. The research method used is through technique. Collect observational data, tests, and documentation of data analysis techniques with 23 subjects, 10 men and 13 women. In cycle I, the research results showed that as many as 12 students passed, the results of student observations were 17.39, the teacher's observations were 71.05, and the test results were 72.56 with a completeness percentage of 52.17% in the good category. In cycle II, 20 students completed, the student observation results were 91.30, the teacher observations were 88.15 and the test results were 81.39 with a completeness percentage of 86.96%, very well. Based on the results of this study it was concluded that the application of the Contextual Teaching and Learning learning model could improve student learning outcomes.